Mengasah Kreativitas Dan Kemandirian Anak MIS Muhammadiyah Bontolangkasa - Nasrawati, Nasrawati; Nur Alifa; Mardiana; Hijriana Ramadani; Andi Ainun Mardiah AS; Taufik Hidayat; Andi Fairus Nizam; Asmaul Husna; Jasri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Children at MIS Muhammadiyah Bontolangkasa are in an important stage of development and therefore need stimulation for creativity and independence. Conventional learning methods that emphasize memorization are considered less effective in developing their potential. This PKM program aims to enhance creativity, independence, and fine motor skills through learning by playing, especially with a bracelet-making workshop. Activities include introducing basic tajwid, waqaf practice, educational games, and bracelet making as a learning medium. Methods used include colored verse cards, board games, animated videos, pocket books, and evaluation through observation and direct practice. The results show increased active participation, creativity, independence, and students’ understanding of tajwid. Teachers and parents gave positive feedback, considering this method effective in fostering enthusiasm for learning and building children’s character. The bracelet workshop also trains fine motor skills, self-confidence, problem solving, and teamwork.